The Role of Madrasah Principal Leadership in Improving Teacher Performance and Student Achievement - Sidiq, Umar; Saleh, Yusuf Yusian Septianto (LETIGES, 2025)
This research is motivated by the phenomenon of teacher performance, which is still less than optimal in managing and implementing learning practices in madrasas. Apart from teacher performance, the role of the madrasa principal also has a major role in improving student achievement, starting from planned and established policies to support facilities and morals for students. The purpose of this study is to analyze the role of madrasah principal leadership in improving teacher performance and student learning achievement at MAN Pacitan. The study uses a qualitative approach with data collection techniques using observation, interviews, and documentation. For data validity techniques, credibility tests should be used with increased perseverance in research, triangulation, and referential adequacy. Data analysis techniques using the theory of Miles, Huberman and Saldana, namely through data collection, data condensation, data presentation, and concluding. The study found that the leadership of the Madrasah principal at MAN Pacitan plays a crucial role in enhancing teacher performance and student achievement. The principal actively supports and motivates teachers by fostering a strong sense of dedication to their profession. This is achieved through continuous professional development, including teacher training, learning workshops, and educational book discussions, which help educators refine their teaching strategies and stay updated with the latest pedagogical advancements. Additionally, the principal implements a strategic approach to student development by analyzing available resources, prioritizing support for students with high potential, and providing targeted mentoring and motivation, particularly during academic and extracurricular competitions.